On the Mean Values of the Dirichlet Series - Zelisko, M. M.; Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
For Dirichlet series with arbitrary abscissa of absolute convergence, we investigate the relationhip between the increase in the maximum term and \(\left( {\mathop \sum olimits_{n = 1}^∞ \left| {a_n } \right|^q \exp \{ qσ λ _n \} } \right)^{1/q}\) , q ∈ (0,+∞).